2018
DOI: 10.1093/gigascience/giy047
|View full text |Cite
|
Sign up to set email alerts
|

SILAC-based phosphoproteomics reveals new PP2A-Cdc55-regulated processes in budding yeast

Abstract: BackgroundProtein phosphatase 2A (PP2A) is a family of conserved serine/threonine phosphatases involved in several essential aspects of cell growth and proliferation. PP2ACdc55 phosphatase has been extensively related to cell cycle events in budding yeast; however, few PP2ACdc55 substrates have been identified. Here, we performed a quantitative mass spectrometry approach to reveal new substrates of PP2ACdc55 phosphatase and new PP2A-related processes in mitotic arrested cells.ResultsWe identified 62 statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 92 publications
5
24
1
Order By: Relevance
“…reported a SILAC based phosphoproteomics study of a PP2A-Cdc55 mutant in which they identified 62 potential Cdc55 substrates [27]. By comparing their results to our list of Isc1 and Cdc55-dependent phosphoproteins, we found a significant overlap of ~29%, strongly supporting the validity of our analysis.…”
Section: Identification Of Isc1 and Cdc55-dependent Dephosphorylationssupporting
confidence: 76%
“…reported a SILAC based phosphoproteomics study of a PP2A-Cdc55 mutant in which they identified 62 potential Cdc55 substrates [27]. By comparing their results to our list of Isc1 and Cdc55-dependent phosphoproteins, we found a significant overlap of ~29%, strongly supporting the validity of our analysis.…”
Section: Identification Of Isc1 and Cdc55-dependent Dephosphorylationssupporting
confidence: 76%
“…Proteome-wide surveys uncovered a plethora of PP2A Cdc55 substrates. Consistent with its biochemical characteristics, PP2A Cdc55 preferentially targets threonine residues, thereby establishing a temporal order of serine before threonine phosphorylation as cells progress from S phase to mitosis (Baro et al., 2018, Godfrey et al., 2017). Little is known about the possible roles of PP2A Rts3 .…”
Section: Introductionmentioning
confidence: 77%
“…Recent phosphoproteomics studies suggest additional roles for PP2A Cdc55 in sensing several internal and environmental cues [144] being important for the septin ring dynamics and morphogenesis checkpoint ( Figure 8 ). Thus, PP2A Cdc55 downregulates Swe1 after septin rings are properly organized, promoting mitotic entry, and it is also involved in the regulation of the septin ring disassembly process [107].…”
Section: Pp2a and Pp2a-like Phosphatasesmentioning
confidence: 99%